Fenton and photo-fenton process to the wastewater treatment of coffee fruits - Kondo, Márcia Matiko; Moraes, Renan Gaspar Magalhães; Andrade, Sandro José de; Silva, Milady Renata Apolinário da (Coffee Science - ISSN 1984-3909, 2014)
Brazil is the largest coffee producer in the world. After the coffee harvest, the coffee cherry goes through some processes with the objective to improve the quality of the coffee. Among these processes the coffee cherries washing and pulping processes generates large amount of wastewater which contains high amount of organic matter. The present study evaluated the efficiency of Fenton and photo-Fenton processes to reduce chemical oxygen demand (COD), biochemical oxygen demand (BOD), total organic carbon (TOC) and color from the coffee pulping wastewater. Wastewater samples from conventional and organic cultures, collected in 2010, were used in these studies. A preliminary characterization of the effluent showed high content of organic matter and acidic pH. The Fenton process showed to be efficient to the removal of organic matter, resulting in a reduction of 92% of COD, 95% of BOD and 69% of TOC. Use of the photo Fenton system resulted in a reduction of 98% of COD, 100% of BOD and 94% of TOC. The reduction of the wastewater color was also observed in both processes.